2018
DOI: 10.1111/ffe.12851
|View full text |Cite
|
Sign up to set email alerts
|

Competition mechanisms of fatigue crack growth behavior in lath martensitic steel

Abstract: The fatigue crack growth behavior in 20CrMnTi lath martensitic steel with a hierarchical structure was investigated at room temperature. The microstructure was quantitatively characterized by optical microscopy, scanning electron microscopy, electron backscattering diffraction, and transmission electron microscopy. Crack growth tests were performed at a stress ratio of 0.1 under the control of a stress intensity factor range using compact tension specimens. The results show that the lath martensite with medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…[6,8,14,24,26] In contrast, however, some studies revealed block boundaries to have the most pronounced barrier effect on short crack propagation. [6,7,26] In the investigation of Koschella et al [7] no impact of PAGBs on short crack propagation could be observed at all, i.e., the crack propagation rate did not slow down appreciably when a fatigue crack approached a PAGB. Rather the crack crossed this boundary unaffectedly, leading to the assumption that the misorientation between the dominating slip systems in the neighboring prior austenite grains is small.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[6,8,14,24,26] In contrast, however, some studies revealed block boundaries to have the most pronounced barrier effect on short crack propagation. [6,7,26] In the investigation of Koschella et al [7] no impact of PAGBs on short crack propagation could be observed at all, i.e., the crack propagation rate did not slow down appreciably when a fatigue crack approached a PAGB. Rather the crack crossed this boundary unaffectedly, leading to the assumption that the misorientation between the dominating slip systems in the neighboring prior austenite grains is small.…”
Section: Discussionmentioning
confidence: 99%
“…[4,8,9,13,24] The subsequent short crack propagation seems to be strongly influenced by the local microstructure, whereby a short crack propagation parallel to the martensitic laths is often observed. [8,24,25] PAGBs [6,8,14,24,26] and block boundaries [6,7,26] seem to act as obstacles for short crack propagation, leading to an oscillating short crack propagation rate. An often referred explanation for the barrier effect of microstructural interfaces is the misorientation between the two main slip…”
mentioning
confidence: 99%
See 3 more Smart Citations